Rotational Flocking with Spontaneous Directional Changes - Xiaolu Liu; Guanbo Shao; Yudong Tang; Duxin Chen (Complexity)
Revealing the underlying decision-making strategy governing the high-group polarization accompanied by conflicting individual preferences may play a central part in the lives of social animals. Hereby, we construct a structured spin model in accordance with empirical validation, which shows how distinct individual preferences converge from one consensus homeostasis to another lowest-energy equilibrium. To verify the theoretical derivation, we use high-resolution spatiotemporal GPS data of a flock of thirty pigeons and study the dynamical evolution mechanism of systemic spins. Therein, we find successful rotational direction transitions requiring a sufficient number of supporters. A few initiators trigger the phase transition from one equilibrium to another, where the symmetric transient state indicates a diamond hierarchical network being completed by the intermediates and the rear individuals. By further studying the nature, we reveal that decision-making sequences are strongly triggered and influenced by individual positions and the leader-follower relationship. Thus, we can predict which individual is more likely to make the decision before the initial transition moment and who will draw the complete stop. Consequently, the revealed decision-making strategy facilitates a comprehensive understanding of collective behavioral transition.